Kartelisasi Sitasi Ditinjau Dari Perspektif Kristen - Darmawan, I Putu Ayub; Ronda, Daniel (Integritas: Jurnal Teologi, 2019)
This article discusses the issue of "citation cartelization" which is viewed from a Christian perspective. A review from a Christian point of view is needed in order to give a view to Christian academics, so that they can take a stand regarding the issue. From the results of the analysis, "citation cartelization" is a citation control measure in an effort to increase the number of citations which ultimately has an impact on increasing index rank in indexing and ranking machines on the Sinta page. In addition, "citation cartelization" is a scientific dishonesty, because efforts to increase the number of citations are carried out by encouraging others to cite one's scientific work even though there is no relevance.